Implementation of Augmented Reality in Social Education: A Literature Analysis of Applications and Benefits - Yamres Pakniany; Heinrich Rakusa (Journal Education Innovation (JEI), 2023)
In an increasingly connected modern era, the implementation of Augmented Reality (AR) technology has opened new doors in social education. The researcher conducted a literature analysis of AR applications in the context of social education and identified the main benefits generated using a qualitative descriptive method through literature study.  The analysis revealed that AR enables more interactive and immersive social learning by providing realistic and interactive simulations of social situations. The benefits of AR in social education include increased student understanding of social issues, increased student engagement, and active participation in social problem solving. However, challenges such as the cost of AR application development and teacher training need to be overcome to maximize the potential of this technology. This research underscores important implications, including the development of more effective learning models, close collaboration with technology developers, and integrated curriculum planning. With a deep understanding of AR applications and their benefits, social education can face a more innovative and effective future, preparing students to play an active role in social change and solving pressing social issues